Internalization of Rabbani Character at Maahad Darulrahmah Pattani Thailand - Surasit Singkhala; Asrori Asrori; Abdunrorma Samaalee; Saiful Anwar; Tobroni Tobroni (CV. Zamron Pressindo, 2024)
This study aims to determine the internalization of the rabbani character practiced in Maahad Maahad Darulrahmah Pattani Thailand. This research uses quantitative research, the subject of this research is Maahad Darulrahmah Pattani Thailand and the object of this research is the process of internalizing the rabbani character. The results of the study: The internalization of the rabbani character practiced in Maahad Darulrahmah Pattani Thailand is based on the thoughts of the Islamic boarding school caretakers which are formulated in the khiththah of Maahad Darulrahmah Pattani Thailand, namely the formation of a rabbani character who has iman and has a rabbani character sincerity as a basis for charity, understanding the correct way of worship, having commendable morals, having good spirituality, having broad scientific insights, having a healthy and strong physique, and having readiness to preach